Unity of Knowledge, Rationality and Tolerance in the Islamic Civilization| الوحدة المعرفية والعقلانية في الحضارة الإسلامية - Abbas Mansur Tamam (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2011)
This study consists of three topics: the unity of knowledge in Islamiccivilization, Islamic rationality as a mechanism of Ijtihad, tolerance andopenness for the new culture. The study confirms that Islam is a God devinethat makes Muslims that passes specific position, guidance, and control uponthe world, and commitment with the principles that direct them to be a leaderin this world. Muslim’s position will be right if it is based on respectablefreedom, high spirit, and free thinking, adopted from the suitable environmentsurrounded with the west. Islam has reliable standard and flexibility ininteraction with the West, Islam can accept or reject, depending on its benefitand its danger, and its suitability with the concept of Islamic Tauhid as theimportant basis of Islamic view. The Study refers to the Quranic texts andHadis texts, as well as it refers to both classical and contemporary books.